Synthesis, Spectral and Thermal Properties of Na/K-Nickel Nitrilotriacetate Hydrazinates - K. Naik, Ganpat; S. Budkuley, Jayant (Asian Journal of Chemistry, 2012)
Bimetal nitrilotriacetate hydrazinate salts with sodium/potassium and nickel metals have been synthesized. Spectral and thermal properties of these salts have been defined. All the three carboxylates of the nitrilotriacteic acid have been found to be dissociated and ionized in these salts.